2022
DOI: 10.2147/jhc.s363123
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Treatments Eliminate the Adverse Impacts of High Baseline HBV Loads on the Survival of HBV-Related HCC Patients

Abstract: Background In consideration of no standard exclusion criteria for hepatitis B virus (HBV) loads in hepatocellular carcinoma (HCC)-related clinical trials, this study aimed to investigate the prevalence of HBV-related exclusion criteria among current clinical trials and evaluate whether antiviral treatments could eliminate the adverse effects from high HBV loads for HCC patients. Methods This is a retrospective study including 772 HCC clinical trials on ClinicalTrials.go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…However, HBV-DNA and HBeAg were not independent risk factors for OS and RFS, possibly due to the administration of anti-HBV treatment to all participants in our study. Some scholars have pointed out that antiviral treatment will improve the negative impact of elevated baseline HBV loads on the prognosis of HBV-related HCC patients (Hu et al, 2022). Interestingly, our findings indicated that younger patients (age<60) exhibited poorer OS compared to older patients (age≥60), which is contrary to many existing studies.…”
Section: Discussioncontrasting
confidence: 99%
“…However, HBV-DNA and HBeAg were not independent risk factors for OS and RFS, possibly due to the administration of anti-HBV treatment to all participants in our study. Some scholars have pointed out that antiviral treatment will improve the negative impact of elevated baseline HBV loads on the prognosis of HBV-related HCC patients (Hu et al, 2022). Interestingly, our findings indicated that younger patients (age<60) exhibited poorer OS compared to older patients (age≥60), which is contrary to many existing studies.…”
Section: Discussioncontrasting
confidence: 99%
“…It is worth mentioning that Hu et al suggested that the prognosis of HBV-related HCC patients with elevated baseline HBV loads could potentially improve after receiving anti-HBV treatment. 46 …”
Section: Discussionmentioning
confidence: 99%
“…Recent research reports that antiviral treatments can eliminate the adverse impacts of high baseline HBV-DNA levels on the survival of HBV-related HCC patients. 37 In recent years, effective antiviral drugs such as entecavir and tenofovir have been applied universally. Most patients in our study received NAs therapy and HBV-DNA levels were under good control, which could illustrate why HBeAg and baseline HBV-DNA levels were not independent risk factors in our study.…”
Section: Discussionmentioning
confidence: 99%